Disappearing daughters : the tragedy of female foeticide - Aravamudan, Gita. (New Delhi : Penguin Books, 2007)
Articles with reference to India.
Includes bibliographical references and index.
Keywords: Abortion -- Social aspects -- India; Fetal death -- Social aspects -- India; Girls -- Crimes against -- India; Abortion -- Moral and ethical aspects -- India; Abortion -- Law and legislation -- India